Condicionadores químicos na compostagem de cama de aviário - Rosa, Jaqueline Kristiane da (2015)
In poultry litter composting process takes place emission of gases, they can reduce the nutritional value of the generated compound.The study aimed to evaluate the effect of different chemical conditioners applied to poultry litter during the maturation process. Two separate experiments were conducted to evaluate the potential conditioner in the dependencies of UTFPR – Dois Vizinhos. Conditioners used were aluminum sulfate and single superphosphate, both applied at rates of 0; 2.5; 5; 7.5 and 10% in a randomized design with three replications, evaluated at different times. It was performed during the maturation process litter reviews pH, temperature, emission of NH3 and CO2. Besides collected during the composting process the litter, to quantify the concentrations of calcium, magnesium, nitrogen, phosphorus, potassium and total carbon. The addition of aluminum sulphate in poultry litter to the process of composting reduced the emissions ammonia and CO2 with increasing doses. The highest values of pH were found in the 0% doses during the composting period. For nitrogen doses 10% aluminum sulphate had the highest concentration reached 27.9 g kg-1, while the dose 0% obtained 22 g kg-1. Calcium concentration decreased at doses 7.5 and 10% compared to dose 0% at 90 days of composting. To magnesium at 90 days showed the highest concentration dose 5% (9.1 g kg-1). The addition of aluminum sulphate decreased phosphorus and potassium levels in the composite. With the use of superphosphate conditioner as lower emissions of ammonia and CO2 were observed at dose of 10%, with 0.08 g of N ammonia m² day-1 and 383.2 g of CO2 day-1 m2.The highest pH values were observed in the dose 0%, averaging 8.6. The concentration of nitrogen and calcium had linear increase with increasing dose, while the magnesium concentration was decreased with increased dose superphosphate. The addition of aluminum sulphate and superphosphate in poultry litter composting process reduce the emission of ammonia and CO2 and contribute to the increase of nitrogen concentration in the composite, providing improvements in chemical quality of the final product for subsequent use in cultures.